Carcinoma of the uterine cervix: a review of its pathology and commentary on the problem in Malaysians - Cheah, Phaik Leng; Looi, Lai Meng (College of Pathologists, Academy of Medicine Malaysia, 1999)
Since its recognition about 150 years ago, there has been much progress in the understanding of the pathogenesis, prevention, early detection and management of carcinoma of the uterine cervix. Important historical landmarks include the (1) recognition of pre-invasive and pre-clinical lesions, and the devise of various systems for reporting these lesions, (2) improvements in diagnostic techniques particularly colposcopy, (3) advent of therapeutic procedures (electrocoagulation, cryotherapy, laser therapy and loop electrosurgical excision), and (4) recognition of the aetiological relationship between the human papillomavirus and cervical neoplasia. The susceptibility of the cervical transformation zone to malignant change is now well recognised. The WHO classification system remains the one most commonly utilised for histological reporting of cervical cancers. In the recent 1994 update, cervical carcinoma is divided into 3 main categories: squamous cell carcinoma, adenocarcinoma and other epithelial tumours. Squamous cell carcinoma (60-80%) predominates among invasive cervical carcinoma. Recognised variants include verrucous, warty (condylomatous), papillary squamous (transitional) and lymphoepithelioma-like carcinoma. Adenocarcinoma (5-15% of invasive carcinomas) shows an increasing trend in young females. Like its squamous counterpart, preinvasive and microinvasive versions are known. Variants such as mucinous, endometrioid, clear cell, mesonephric, serous, villoglandular and minimal deviation carcinoma are now defined. Adenosquamous carcinoma (5-25%), adenoid-cystic, adenoid-basal, neuroendocrine and undifferentiated carcinomas constitute other epithelial tumours of the cervix. The management of invasive cervical carcinoma remains heavily dependent on its stage. The FIGO staging system remains the most widely used. The 1995 update provides more definite criteria in subdividing stage IA tumours by delimiting stromal invasion of stage IA1 lesions to a maximum depth of 3 mm and a horizontal axis of 7 mm. In Malaysia, an appreciation of the cervical carcinoma problem has to take into consideration the population at risk, its multi-ethnicity, its socio-economic and geographical diversities and the constraints of the health care system. Females form 48.9% of the Malaysian population. 52.9% of them are in the sexually active age group of 15-50 years, indicating a significant population at risk for cervical carcinoma. Cervical carcinoma was the third most common cause of death due to solid tumours among Malaysian females in 1995 following carcinoma of the breast and respiratory tract. East Malaysia is predominantly rural with many communities having limited modern facilities. Such areas imply a lower educational and socio-economic status, raising the worry of a population at higher risk for developing cervical carcinoma. The population: doctor for Malaysia of 2153:1 compares poorly with nearby Singapore. Besides a shortage of doctors, there is also an uneven distribution of doctors, resulting in a ratio in East Malaysia of > 4000:1. Although Malaysia does not have a national cervical cancer-screening programme, many action plans and cancer awareness campaigns have been launched throughout the years, which appear to have made an impact as evidenced by the decreasing mortality rates from cervical carcinoma. Another interesting feature of cervical carcinoma in Malaysia relates to its multiethnic population. In Malaysian Chinese and Malay females, the prevalence of cervical carcinoma ranks second to breast cancer whereas the pattern is reversed in Malaysian Indian females. Studies into its aetiology and pathogenesis are being undertaken and may shed more light on this matter.